The Complementary Role of Family, Religion, and Spiritual Intelligence in Reducing Addiction Susceptibility: A Study on the Mediating Role of Psychological Well-Being - Moazami Goudarzi, Soheil; Azemoudeh, Masoumeh; Hoseini Nasab, Seyyed Davoud (Mental Health and Lifestyle Journal, 2024)
Identifying factors associated with addiction susceptibility among students can significantly contribute to the prevention of drug use tendencies. Accordingly, the present study aimed to examine and analyze the complementary role of the family in addiction susceptibility, based on family cohesion, religious values, and spiritual intelligence, while testing the mediating role of psychological well-being. This study employed a quantitative approach. Data were collected using a standardized questionnaire administered to a statistical population comprising students of the Islamic Azad University in Tehran. The data analysis method utilized was multivariate regression analysis. The results from the multivariate regression analysis indicated that all three factors—family cohesion, religious values, and spiritual intelligence—can predict addiction susceptibility among the youth in this study. Moreover, psychological well-being was found to play a mediating role in these relationships.